Modeling the Separating Pedestrian Flow in T-Shaped Passage Based on Guide Sign - Hong-fei Jia; Yong-xing Li; Li-li Yang; Ya-nan Zhou (Discrete Dynamics in Nature and Society)
Considering the actual situation of separating pedestrian flow in T-shaped passage, the guide sign is set to guide the pedestrians and subconscious strength is introduced to show the effect of guide sign. Pedestrian subconscious strength model is established, and the subconscious strength calculation result is added to the pedestrian simulation model which is based on cellular automata. On the platform of MATLAB software, separating pedestrian flow simulation with the effect of guide sign is realized. Simulations indicate that, compared with the separating pedestrian flow without guide sign, the efficiency of pedestrians passing with guide sign is higher. Analyzing the effect of guide sign in different positions, the suitable position of guide sign is obtained.